Pemberdayaan petani karet rakyat dalam mengendalikan penyakit jamur akar putih dengan teknologi biofungisida tepung berbahan aktif Trichoderma virens endofit di Kecamatan Mempura Kabupaten Siak - Fifi Puspita; Adiwirman Adiwirman; Elza Zuhry; Muhammad Ali; Erlida Ariani; Kausar Kausar; Rachmad Saputra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
Community service activities in the form of activities of Desa Binaan through the application of biofungicide technology of Trichoderma virens endofit formulation in powder formulas was carried out at Lubuk Betuah Farmer Group, Pelimauan Jaya and Anugrah in Teluk Merempan Village Mempura District of Siak Regency. The purpose of this activity is to increasing knowledge of farmer groups in the formulation of Trichoderma virens endophytes in powder formulas and producing environmentally-friendly powder biofungicides so as to increase the production and quality of latex, in addition to ease the burden of farmers on fertilizer needs. From this activity is concluded several things, that are socialization of technology control program R. microporus in farmers group target 100% not knowing the use of T. virens as biofungisida. Training on the manufacture of flour biofungicide and the way biofungicide application for control of R. microporus 50% of the target farmer group has the desire to use T. virens biofungicide. Assistance of making flour biofungiside all the participants can make flour biofungicide. Next year activity is done monitoring and evaluation result of R. microporus control and mass production of flour biofungiside for increase the income of rubber farmers.